Application of new technologies and materials on the M-12 motorway - S. V. Privezentseva; А. F. Ivanov (Vestnik MGSU)
Introduction. The significance of the M-12 motorway under construction as an international transport route is analyzed. The expediency of the project implementation based on the interests of Russia is noted.Materials and methods. Structural solutions for the roadway on the M-12 motorway were considered. Materials for each structural and functional layer of the roadway are given. A brief review of the experience of using asphalt concrete designed using the Superpave method abroad and in Russia is provided. The question of inefficient arrangement of expensive by composition and complicated by design technology layers of new asphalt concrete inside rather than in the cover of the pavement structure on the M-12 motorway is raised.Results. Advantages and disadvantages of the Superpave technology are shown. The peculiarities of bituminous binder selection are analyzed. Organizational, constructive, material and technological measures for the implementation of the design granulometric composition of the mineral part in the technology of asphalt concrete by the Superpave method are presented. The reasoned criticism of application of a new type of bituminous binder and granulometric composition of asphalt concrete according to the Superpave method is given.Conclusions. The necessity of further study and development of the technology of asphalt concrete by the Superpave method and materials with superabsorbent polymer additives for their effective application is noted. The issues of ensuring workability of materials with polymer additives and regulation of their application by standards are outlined.